2003
DOI: 10.1016/s0926-6410(02)00149-0
|View full text |Cite
|
Sign up to set email alerts
|

Is human sentence parsing serial or parallel?

Abstract: In this ERP study we investigate the processes that occur in syntactically ambiguous German sentences at the point of disambiguation. Whereas most psycholinguistic theories agree on the view that processing difficulties arise when parsing preferences are disconfirmed (so-called garden-path effects), important differences exist with respect to theoretical assumptions about the parser's recovery from a misparse. A key distinction can be made between parsers that compute all alternative syntactic structures in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…This would follow findings with linguistic stimuli where extremely ungrammatical sentences do not elicit at P600 response (see Hopf, Bader, Meng, & Bayer, 2003). This might also explain Demiral et al's (2012) lack of P600 responses, while they instead observed early N300-N400 effects.…”
Section: Discussionsupporting
confidence: 78%
“…This would follow findings with linguistic stimuli where extremely ungrammatical sentences do not elicit at P600 response (see Hopf, Bader, Meng, & Bayer, 2003). This might also explain Demiral et al's (2012) lack of P600 responses, while they instead observed early N300-N400 effects.…”
Section: Discussionsupporting
confidence: 78%
“…If the parser is ranked parallel, then the relatively high frequency of subject relatives could facilitate processing even in the pre-head noun regions, where the most probable structure is a non-RC. Although the serial versus parallel parser issue was never really resolved in the literature [53][55], we follow [56], and [37], [10][11] in assuming a ranked parallel parser. Under this view, multiple possible structures are maintained in memory but with different ranks (determined by the probability of each parse).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this is consistent with the neural activity we observe in the striatal readout neurons – multiple parses are maintained, based on their probability within the corpus – analogous to the notions of “preferred” and “non-preferred.” These results are pertinent within the psycholinguistics community, where a debate continues concerning whether human sentence processing is based on always maintaining the single, best current parse candidate (serial processing) or rather, maintaining multiple open options, and pruning and updating these options as the sentence unfolds (parallel processing) [22], [60], [61]. One of the arguments against parallel processing is related to the cost and difficulty of maintaining multiple, parallel parses.…”
Section: Discussionmentioning
confidence: 99%